2018
DOI: 10.12681/jhvms.18879
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the bovine IGF1, TG, DGAT1 and MYF5 genes to meat colour, tenderness and cooking loss

Abstract: Bovine insulin-like growth factor 1 (IGF1), thyroglobulin (TG), diacylglycerol-O-acyltransferase 1 (DGAT1) and myogenic factor 5 (MYF5) genes play an important role in the physiology of lipid and muscle metabolism and are therefore considered as candidate genes for meat production traits in farm animals. The objectives of this study were to investigate single nucleotide polymorphisms (SNPs) in IGF1, TG, DGAT1 and MYF5 genes and to evaluate whether these polymorphisms affected meat colour, tenderness and cookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Lysine (K)→ alanine (A) was detected on exon 8 of DGAT1 gene of Bos taurus: (Figure 3) (21,22,45). Later on, many studies documented the significant association of DGAT1 K232A polymorphism with milk production traits in dairy cattle (45)(46)(47)(48)(49). The DGAT1 region analysis in six Indian cattle (Sahiwal, Rathi, Deoni, Tharparkar, Red Kandhari, and Punganur) revealed fixed DGAT1 K allele (Figure 3) (45).…”
Section: Dgat1 K232a Association With Milk Production In Cattlementioning
confidence: 98%
See 1 more Smart Citation
“…Lysine (K)→ alanine (A) was detected on exon 8 of DGAT1 gene of Bos taurus: (Figure 3) (21,22,45). Later on, many studies documented the significant association of DGAT1 K232A polymorphism with milk production traits in dairy cattle (45)(46)(47)(48)(49). The DGAT1 region analysis in six Indian cattle (Sahiwal, Rathi, Deoni, Tharparkar, Red Kandhari, and Punganur) revealed fixed DGAT1 K allele (Figure 3) (45).…”
Section: Dgat1 K232a Association With Milk Production In Cattlementioning
confidence: 98%
“…Many studies have investigated the effect of DGAT1 gene on meat production traits in beef cattle (4,5,48,131). The role of DGAT1 gene for production traits has also been reported in seven cattle breeds (Angus, Belgian Blue, Charolais, Hereford, Holstein-Friesian, Limousin, and Simmental cattle) (132).…”
Section: Dgat1 Association With Meat Production Traits In Cattlementioning
confidence: 99%
“…In addition, CC genotype in Polish Holstein had higest of body weight at two months and average daily gain from one to two months (Szewczuk et al 2013). Ardicli et al (2018) reported that the CC genotype had the best of meat colour score at 24 hours post-slaughtering in FH bull. The CC genotype in the present study was detected in all samples and can be suggested as the common genotype for Pasundan cattle.…”
Section: Resultsmentioning
confidence: 95%
“…Polymorphism in IGF1/SnaBI was affected to the productivity traits of cattle i.e. body weight at three months in Hanwoo cattle (Chung & Kim 2005), serum concentration of IGF1 at 14 days post partum in Friesian Holstein (FH) cattle (Mirzaei et al 2012), service per conception and days open in FH cattle (Ararouti et al 2013), breeding value of milk and fat yields in Iranian Holstein bulls (Mehmannavaz et al 2010), growth traits in beef cattle (Siadkowska et al 2006;Reyna et al 2010;Szewczuk et al 2013), carcass traits (Reyna et al 2010) and meat colour in FH bulls (Ardicli et al 2018). This research was aimed to detect SNP in the exon 1 of IGF1/SnaBI gene in Pasundan cattle using PCR-RFLP method.…”
Section: Introductionmentioning
confidence: 99%
“…The thyroglobulin 5′ leader sequence (TG5) gene is one of the longest mammalian genes. In cattle, it is located in the centromere region of the 14 th chromosome and consists of 37 exons [6][7][8][9]. The TG5 gene has two allelic variants, TG5 T and TG5 C , and three genotypes, TG5 CC , TG5 CT , and TG5 TT .…”
Section: Introductionmentioning
confidence: 99%